Two approaches to the myth of city foundations: Syntagmatic and paradigmatic - Nastopka, Kestutis (Sign Systems Studies, 2002)
The paper discusses the myth of the founding of Vilnius as an example of a myth of city foundation. The myth has received two independent semiotic interpretations. Narrative grammar procedures are applied to the analysis of the mythical story and the semantic code generating the story in the paper “Gediminas’ Dream (Lithuanian myth of city foundation: an attempt at analysis)” by Algirdas Julien Greimas (1971). The sovereignty ideology expressed in the myth, which describes religious and spiritual culture of the Grand Duchy of Lithuania, is linked to the tri-functional model of the IndoEuropean social structure. The semantics of the Vilnius myth is seen as analogous with such Indo-European myths as king’s accession to the throne and creation of a city-state. The Lithuanian myth of Vilnius is linked paradigmatically to the Indo-European mythology in the study “Vilnius, Wilno, Vil’na: City and myth” by Vladimir Toporov (1980). At the level of the signifier, phonological equivalents of toponyms of Vilnius are traced. At the level of the signified, transformations of the “core” Indo-European myth are identified. The myth of the city foundation can be read both as a figurative form of cultural expression and as an ideology narrated as a plot of a story. In this view, the paradigmatic and syntagmatic approaches complement each other.